Head and Neck Manifestations of Granulomatosis with Polyangiitis: A Retrospective analysis of 19 Patients and Review of the Literature - Carnevale, Claudio; Arancibia-Tagle, Diego; Sarría-Echegaray, Pedro; Til-Pérez, Guillermo; Tomás-Barberán, Manuel (International Archives of Otorhinolaryngology, 2019)
Introduction Granulomatosis with Polyangiitis (GPA) is a small vessel vasculitis characterized by a necrositing granulomatous inflammation of the upper and lower respiratory tracts and focal/proliferative glomerulonephritis. In more than 70% of the cases, the presenting symptoms are head and neck manifestations that are often misdiagnosed as infectious or allergic in etiology.Objective The present study provides an analysis of head and neck manifestations in a series of patients diagnosed with GPA. It also evaluates their medical and surgical treatment and provides a review of the relevant literature.Methods A retrospective analysis of 19 patients diagnosed with GPA at a public tertiary care hospital between 2006 and 2017 was performed.Results A total of 19 patients were included in the present study, and 16 of them presented head and neck manifestations. Sinonasal symptoms were the most common, affecting 56% of the patients, followed by laryngotracheal (31.25%) and ear (25%) symptoms. In 7 patients, sinonasal symptoms were the first manifestation of the disease (43.75%). Four patients underwent surgery at some stage of the disease.Conclusions Head and neck involvement is common in GPA and may stand for the first or the only manifestation of the disease. The otolaryngologists play a central role in the diagnosis and long-term treatment of these patients, and they have to keep this pathology in mind when treating patients with ENT symptoms that do not respond as expected to the treatment.
Keywords: granulomatosis with polyangiitis; vasculitis; anti-neutrophil cytoplasmic antibodies